Impact of remote collaboration-based family physical activity on activity levels and quality of life in children with intellectual developmental disabilities - Xin Shen; Peiying Huang; Maolin Su; Zijuan Liu; Qian Liu; Yin Guo; Lan Zheng (Frontiers Media S.A., 2024)
BackgroundLow levels of physical activity (PA) are prevalent among children with intellectual and developmental disabilities (IDD). Implementing family-based physical activities as extracurricular interventions offers a promising approach to enhancing their PA levels and promoting overall health.PurposeThis study aims to explore a novel integrative strategy by combining family-based activities with school physical education classes, with the objective of enhancing PA levels and improving the quality of life (QoL) for children with IDD. Methods: A total of 36 children with IDD (mean age = 16.4 years) were randomly assigned to a 6-month intervention group (IG) or a control group (CG). Both groups received adjusted adaptive physical education, while the IG received additional family support. Assessments of PA, QoL, and the Physical Activity Enjoyment Scale (PACES) were conducted at baseline, after 6 months, and at a 2-month follow-up post-intervention.ResultsThe 6-month intervention results showed that the IG had a significant increase in moderate to vigorous physical activity (MVPA) compared to the CG (p < 0.001, d = 3.87) and a reduction in sedentary behavior (p < 0.001, d = 2.28). Additionally, there were improvements in WHOQOL-DIS scores (p < 0.001, d = 1.61) and PACES scores (p < 0.001, d = 1.14). At the 2-month follow-up, the IG also showed significant improvements in MVPA, sedentary behavior, and PACES scores, all with p-values below 0.001, while no significant change was observed in WHOQOL-DIS scores (p = 0.914).ConclusionFamily-based physical activities facilitated through remote collaboration not only improved the PA levels of children with IDD and enhanced their quality of life, but also positively contributed to the maintenance of long-term healthy behaviors.